Challenges and opportunities in the use of e-gov platforms: perspectives of retired public servants and pensioners - De Pietre, Patricia Curbani; Freitas, Rodrigo Randow de; Campos, Adriana Fiorotti (Brazilian Journal of Production Engineering, 2025)
Smart cities are based on the use of information and communication technologies (ICTs) to improve the quality of life of citizens in the provision of public services. In this context, e-gov stands out, which seeks to promote efficient delivery; however, the issue of accessibility for users emerges as a basic concern. The objective of the study was to analyze how the services provided by e-gov can be more accessible to retired public servants and pensioners. A systematic literature review was carried out, using bibliometric analysis to identify trends, patterns, and gaps. A significant discrepancy was revealed between citizens' preference for traditional communication channels, such as telephone and in-person service, and the digital strategies adopted by governments, which aim at the cost efficiency of digital channels. Resistance to digitalization is exacerbated by challenges such as lack of familiarity with digital technologies and the need to simplify digital interfaces. Although the need to improve the experience, trust, and accessibility was identified, no studies were found that addressed all topics in an integrated manner. Thus, it is suggested that there is a need for further exploration, focusing on strategies to overcome resistance to digitalization, balance digital efficiency and accessibility, and adapt successful smart city practices to improve technological infrastructure and urban planning.
Keywords: Smart Cities; User Opinion; Public Governance; Electronic Government